Experiments on Soil Microcosms for The Assessment of Greenhouse Gases Fluxes from Different Land Uses in Laboratory Conditions - Laslo Lucian; Enache Natalia; Matei M.; Boboc M.; Radu Alexandru; Ramli Norazrin (E3S Web of Conferences, 2024)
The importance of greenhouse gas (GHG) fluxes in ecosystematmosphere exchanges has grown due to climate change impacts. Achieving climate neutrality by 2050 requires emission reduction and removals, with land use contributing the most. Despite the advance of techniques to quantify GHG dynamics and their involved parameters, it is still uncertain how GHG fluxes respond to changes in each involved parameter, especially for in-situ conditions. Soil moisture and temperature are important parameters in relation to GHG fluxes, with a high degree of natural variation and influence from climate change. With the aim to establish the sensitivity of GHG fluxes for different soil types to natural and anthropogenic variations of parameters, experiments can be conducted in laboratory conditions with efficient resource allocation. Soils were sampled from parcels of long term in-situ monitored lands and large pots were prepared to create microcosms for tests in laboratory conditions. The results of GHG flux monitoring (CO2) are presented in relation to soil moisture as a result of precipitation simulations by water applications on selected microcosms (from agricultural crops and abandoned land). The laboratory results are also compared with field measurements from the same parcels, realised in a period with similar precipitation quantities and temperatures. The presented results constitute the starting point for the laboratory tests on soils, verified by field data, with the aim of establishing the most suitable intervals of parameters for performant land use and carbon removal.